Recyclable optical bioplastics platform for solid state red light harvesting via triplet–triplet annihilation photon upconversion. Issue 40 (5th September 2022) - Bharmoria, Pankaj; Edhborg, Fredrik; Bildirir, Hakan; Sasaki, Yoichi; Ghasemi, Shima; Mårtensson, Anders; Yanai, Nobuhiro; Kimizuka, Nobuo; Albinsson, Bo; Börjesson, Karl; Moth-Poulsen, Kasper
Abstract : Sustainable red light harvesting has been achieved in recyclable protein–surfactant–chromophores co-assembled bioplastics with high efficiency due to the efficient diffusion of triplet excited chromophores, and oxygen blockage by protein fibers. Abstract : Sustainable photonics applications of solid-state triplet–triplet annihilation photon upconversion (TTA-UC) are limited by a small UC spectral window, low UC efficiency in air, and non-recyclability of polymeric materials used. In a step to overcome these issues, we have developed new recyclable TTA-UC bioplastics by encapsulating TTA-UC chromophores liquid inside the semicrystalline gelatin films showing broad-spectrum upconversion (red/far-red to blue) with high UC efficiency in air. For this, we synthesized a new anionic annihilator, sodium-TIPS-anthracene-2-sulfonate (TIPS-AnS), that combined with red/far-red sensitizers (PdTPBP/Os( m -peptpy)2 (TFSI)2 ), a liquid surfactant Triton X-100 reduced (TXr) and protein gelatin (G) formed red/far-red to blue TTA-UC bioplastic films just by air drying of their aqueous solutions. The G-TXr-TIPS-AnS-PdTPBP film showed record red to blue (633 to 478 nm) TTA-UC quantum yield of 8.5% in air. The high UC quantum yield has been obtained due to the fluidity of dispersed TXr containing chromophores and oxygen blockage by gelatin fibers that allowed efficient diffusion of triplet excited chromophores. Further, the G-TXr-TIPS-AnS-Os( m -peptpy)2 (TFSI)2 bioplastic film displayed far-red to blue (700–730 nm to 478 nm) TTA-UC, demonstrating broad-spectrum photon harvesting. Finally, we demonstrated the recycling of G-TXr-TIPS-AnS-PdTPBP bioplastics by developing a downstream approach that gives new directions for designing future recyclable photonics bioplastic materials.